Transforming rural education in Colombia through family participation: The case of school as a learning community - Soler, Marta; Morlà-Folch, Teresa; García-Carrión, Rocío; Valls, Rosa (JSSE - Journal of Social Science Education, 2020)
Purpose: This article studies the impact of the implementation of learning communities in a rural context of Colombia, specifically concerning the improvements related to learning and social cohesion. Design/methodology/approach: This longitudinal case study analyses the process and the impacts of the transformation of a school in 2015 and the subsequent years of 2016 and 2017. The data analysed include standardized external tests, a documentary analysis of the school and interviews with students, family members and the schoolteacher. Findings: The results obtained indicate academic improvement within the school with results that exceed the national average of Colombia. The results also report how violence has been reduced by 80%. All of these outcomes were motivated by the participation of the community in the school. Practical implications: The conclusions drawn are relevant as they show a success case that overcame the difficulties related to the lack of accessibility and quality of rural education in Colombia.